sina+cosa=1/5
1)
(sina+cosa)^2=1/25
sinacosa=-12/25
2)(sina+cosa)^2=(sina-cosa)^2+4sinacosa=1/25
(sina-cosa)^2=1/25-4sinacosa=1/25+48/25=49/25
sina-cosa=7/5 或 sina-cosa= -7/5
sina+cosa=1/5
sina=4/5 cosa=-3/5
tana=sina/cosa=-4/3 或3/4
3)由(2)得
sina-cosa=7/5 或 sina-cosa= -7/5
4)sin^3a+cos^3a=(sina+cosa)^3-3sinacosa(sina+cosa)
=1/125+[12/25*1/5]
=13/125
5)sin^2a+cos^2a=(sina+cosa)(sina-cosa)=1/5*7/5=7/25 或-7/25
6)sin^3a-cos^3a=(sina-cosa)^3+3sinacosa(sina-cosa)
=(7/5)^3-36/25*7/5
=-11/125
sin^3a-cos^3a=-11/125 或 11/125